Traceability in Brazilian cattle: conditions and benefits - Almeida, Juliano; Francischini, Ricardo .; Silva , Frederico Fonseca da; Bett, Vanderlei (Pubvet, 2019)
The objective of this work was to highlight the use of traceability in beef production and to raise the positive aspects of this technology in the complex. The implementation of traceability in Brazil has caused changes in the habit of cattle ranchers, who have to adapt to SISBOV (Brazilian System of Identification and Certification of Bovine and Bubaline Origin). Thus, to determine the conditions that led to the implementation of traceability in beef production stages in Brazil, to describe the traceability process carried out in other countries, to present methodology for implementation of traceability in rural beef cattle producers and to survey impacts of the traceability adoption process and its implications on beef commercialization. It was evident the need for cattle tracking in the country, aiming to adapt to the new demands of the more demanding and segmented consumer market.